High mechanical properties of super aligned carbon nanocomposite by polyurethane based crosslinking molecules - Moon, Sook Young; Kim, Woo Sik (ELSEVIER SCI LTD, 2018)
The interfacial bonding strongly influences the mechanical properties of composite materials. In this study, a polyurethane (PU)-based adhesive material reacted as an interfacial material between carbon nanotubes (CNTs) and an epoxy matrix while simultaneously functioning as a jointing material between CNTs. This synergistic strengthening effect enhanced the mechanical properties of the CNT-epoxy composite. The PU molecules enveloped and bonded well with the CNT surface, as revealed by transmission electron microscopy and Fourier transform infrared spectroscopy. The tensile strength of the composite materials with PU-grafted CNTs was enhanced approximately twofold to 316 MPa, which is substantially greater than that of the composite reinforced with uncoated CNTs (165 MPa). In addition, the tensile strain increased from 0.58% to 0.62% in the composite materials with PU-grafted CNTs.
Keywords: NANOTUBE-POLYMER COMPOSITES; SURFACE MODIFICATION